2017
DOI: 10.1039/c6em00569a
|View full text |Cite
|
Sign up to set email alerts
|

Unexpectedly high concentrations of monoterpenes in a study of UK homes

Abstract: The abundance of volatile organic compounds (VOCs) found in homes depends on many factors such as emissions, ventilation and the oxidative environment and these are evolving over time, reflecting changes in chemical use, behaviour and building design/materials. The concentrations of VOCs in 25 UK homes of varying ages, design and occupancy were quantified using continuous indoor air sampling over five days. Air was collected through low flow (1 mL min) constant flow restrictors into evacuated 6 L internally si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 51 publications
(30 reference statements)
1
30
0
Order By: Relevance
“…In a large survey performed in England, Raw and collaborators registered concentrations of d-limonene from 0.1 to 308 µg/m 3 , with an average geometric mean of 6.2 µg/m 3 [51]. A more recent study carried out in English residential buildings showed concentration values between 18 and 1439 µg/m 3 , with one of the highest domestic values reported in the literature for d-limonene [4]. In the AIRMEX study, the authors identified α-pinene and d-limonene as being predominantly derived from indoor sources, with mean concentrations of 14.5 and 29.2 µg/m 3 observed in homes, respectively [18].…”
Section: Comparison Of Vocs Concentrations With Other Studiesmentioning
confidence: 94%
See 2 more Smart Citations
“…In a large survey performed in England, Raw and collaborators registered concentrations of d-limonene from 0.1 to 308 µg/m 3 , with an average geometric mean of 6.2 µg/m 3 [51]. A more recent study carried out in English residential buildings showed concentration values between 18 and 1439 µg/m 3 , with one of the highest domestic values reported in the literature for d-limonene [4]. In the AIRMEX study, the authors identified α-pinene and d-limonene as being predominantly derived from indoor sources, with mean concentrations of 14.5 and 29.2 µg/m 3 observed in homes, respectively [18].…”
Section: Comparison Of Vocs Concentrations With Other Studiesmentioning
confidence: 94%
“…The indoor air quality (IAQ) is strictly dependent on the occurrence of several chemicals, or classes of chemicals, among which volatile organic compounds (VOCs) represent one of the most important categories of pollutants influencing the air quality, and consequently, human well-being and health [1][2][3][4]. VOCs are classified as organic compounds having a boiling point between 50 • C and 260 • C. These compounds can be emitted into the atmosphere from anthropogenic or biogenic sources, and may also be formed as products of the atmospheric transformation of other VOCs [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Its formation indoors has been documented following the use of limonene containing cleaners. 13 However, for many of the secondary products formed indoors, there is very little information about their typical indoor concentrations and at what concentration they become a cause for concern.…”
Section: Introductionmentioning
confidence: 99%
“…Terpenes are also known to be emitted from building materials (Allen, Brewer et al 2016) and household products, in which they are primarily used as fragrances and flavourings (Wolkoff, Schneider et al 1998, Lamorena and Lee 2008, Steinemann, MacGregor et al 2011, Wang, Barratt et al 2017, impacting indoor air quality (Singer, Destaillats et al 2006, Nazaroff andGoldstein 2015). In particular, the exposure of the public to terpenes in indoor air quality is poorly understood due to a lack of available data, despite the toxicity of their photochemical products (Jones 1999, Wolkoff and Nielsen 2001, Wang, Ang et al 2007, Wang, Barratt et al 2017.…”
Section: Introductionmentioning
confidence: 99%